THE ASSET MANAGEMENT IN HIGHWAYS AND WATER RESOURCES DEPARTMENT SANGGAU REGENCY - Yuli, Marista; Kusnadi, Dedi; Triyono, Joko (PublikA Jurnal Ilmu Administrasi Negara (e-Journal), 2023)
This study aimed to discover the procedures of asset management in the Highways and Water Resources Department in Sanggau Regency and give more effective and efficient alternatives in using the asset, such as tools and machines. This research used descriptive study and qualitative approach with Miles and Huberman’s model data analysis. This research used the Siregar’s (2018, 518-520) asset management theory which consist of asset inventory, legal audit, asset assessment, asset optimization, and control and supervision. The research findings showed that the real condition of tools and machines were not match the data from t